Johannes Horstmanns genoptagelse af Søren Kierkegaards paradokskristologi - Müller, Mogens (Dansk Teologisk Tidsskrift, 2009)
A Danish theologian, Johannes Horstmann (1915-99), belonging to the movement Tidehverv, reacted in the years 1959-68 in a series of articles on the new quest of the historical Jesus initiated by Ernst Käsemann i 1953. He did so by reviving Søren Kierkegaard’s paradox christology, showing that if form criticism is taken to its logical end, no historical Jesus will be left to the historian. In stead consequent criticism will have as its result that the gospels are testimonies of Christ and that their content considered as history is absurd. Thus, to Horstmann, every quest of the historical Jesus is theological illegitimate, because they fail to appreciate the unique character of the gospels.